KOMODIFIKASI GUDEG YOGYAKARTA DAN PENGEMBANGAN DALAM INDUSTRI PARIWISATA - Sunar . (Pusat Penelitian & Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2017)
Indonesian Tradisional Culnery is deversities, but not syatemimatic dodumented yet, becouse its have limited information. This is a study of Gudeg yogyakarta from as a tradisional food until become a trade markfood of yogyakarta. The rusult of studied is that Gudeg yogyakarta is a tradisional food orignal from country (vilage), move to city food, until as a culinery touirist object, and as a comodities. Gudeg Yogyakarta devlope as a market needs especially in cooking and packaging. The taste is kept orginally, from the gudeg with saouce until is made dried (souted gudeg) gudeg yogyakarta. The packaging from “pincuk” made from banana leaf, “besek” made from bamboe plaited, until caned gudeg. The caned Gudeg Yogyakarta is indicated that gudeg yogyakarta is comidificated as a change worth.